Emerging monoclonal antibodies against Clostridium difficile infection. (3rd April 2017) - Péchiné, Séverine; Janoir, Claire; Collignon, Anne
ABSTRACT: Introduction : Clostridium difficile infections are characterized by a high recurrence rate despite antibiotic treatments and there is an urgent need to develop new treatments such as fecal transplantation and immonotherapy. Besides active immunotherapy with vaccines, passive immunotherapy has shown promise, especially with monoclonal antibodies. Areas covered : Herein, the authors review the different assays performed with monoclonal antibodies against C. difficile toxins and surface proteins to treat or prevent primary or recurrent episodes of C. difficile infection in animal models and in clinical trials as well. Notably, the authors lay emphasis on the phase III clinical trial (MODIFY II), which allowed bezlotoxumab to be approved by the Food and Drug Administration and the European Medicines Agency. They also review new strategies for producing single domain antibodies and nanobodies against C. difficile and new approaches to deliver them in the digestive tract. Expert opinion : Only two human Mabs against TcdA and TcdB have been tested alone or in combination in clinical trials. However, many animal model studies have provided rationale for the use of Mabs and nanobodies in C. difficile infection and pave the way for further clinical investigation.